El juego como herramienta diagnóstico en casos de violencia intrafamiliar con niños y niñas beneficiarios del Taller de Apoyo Escolar del Centro de Desarrollo Comunitario Espejo - Chiliquinga Montenegro, Andrea Carolina (2015)
This research was developed in Quito, in the “Centro de Desarrollo Comunitario”, that is part of Quito´s City Hall. Its target was the children that participated in the academic support workshops. During a diagnostic process, domestic violence was pointed out as one of the main problems inside the community and children were the most affected part of the population. When talking to the children in the community, the only possible answers were silence an evasive behavior, so the means to reach children and identify violent situation in their everyday life had to be different from those used on adults. Playing with kids, far beyond considering it as merely a game, can be used as a successful tool for diagnostic processes since playing allows children to express fantasies, wishes, hopes, experiences and fears around the conflict they are going through, so it can show unconscious content that is part of the internal world of the children and builds the way they see external world. In this research, playing is used as a projective tool, a technical resource that allows approaching children in order to see what is there and cannot be seen by the naked eye, domestic violence, in a way that children would not feel threatened by what they might or are allowed to say. As a projective technique, it has a semi structured characterization that can show how the subject represents conflicts. From interpretative hypothesis quality and content can be analyzed until getting to the analysis of domestic violence.